The Effect Of Accounting Information Systems And Internal Control On Employee Performance In Sendang Rejo Village, Langkat Regency - Aditya, Muhammad Haikal; Ramadhan, Puja Rizqy; Azzahra, An Succi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the influence of Accounting Information Systems (AIS) and Internal Control on Employee Performance in Sendang Rejo Village, Langkat Regency. The research background is the existence of digital competency gaps among village employees in operating the Village Financial System (Siskeudes) which impacts performance decline. The research method uses an associative quantitative approach with a sample of 31 village employees. Data were collected through Likert scale questionnaires (1-5) and analyzed using multiple linear regression with SPSS. The results show that AIS has a positive and significant effect on employee performance with a regression coefficient of 0.269 (sig. 0.002 < 0.05), Internal Control has a positive and significant effect with a regression coefficient of 0.532 (sig. 0.000 < 0.05) with a more dominant influence. Simultaneously, both variables have a significant effect with an R-square value of 83.4%, indicating that the combination of Siskeudes implementation with adequate internal control creates synergy in improving employee performance. The study recommends regular Siskeudes training, strengthening internal control through periodic evaluations, and improving technological infrastructure.